Generation, characterization, and comparison of human exhaled and technical aerosols for the evaluation of different air-purifying technologies against infectious aerosols. Issue 10 (2nd November 2022) - Penner, Thomas; Berger, Simon; Niessner, Jennifer; Dittler, Achim
Abstract: In light of the COVID-19 pandemic, the importance of protective measures against infectious aerosols has drastically increased, as the transmission of diseases via airborne particles is impacting many aspects of everyday life. The protective measures against such infections are determinant in the operation of schools and kindergartens, hygiene in hospitals and medical facilities, in offices, administrative and production facilities, hotels, and the event industry, among others. To test these protective measures, suitable test aerosols and processes are needed. These aerosols ought to be similar to aerosols exhaled by humans as those carry the pathogens and thus need to be removed from the air or inactivated. The exhaled aerosols of several healthy test subjects were characterized by their particle concentration and size distribution. In previous studies, it was found that exhaled particle concentration varies significantly from subject to subject and most of the particles can be found in the submicron size range. Aerosols technically generated through nebulization were emitted by the generators in particle concentrations several orders of magnitude higher than those exhaled by humans, independent of the aerosol generation method and nebulized fluid. The particle size distribution generated by the two nebulizers used, however, was quite similar to the measured size distributions of the human aerosols, with most of the particles below 1 µm in size. Consequently, the used aerosol generators are not suitable to mimic single individuals as active aerosol sources, but rather to provide a sufficient amount of aerosol similar to human aerosols in size distribution, which can be used in the testing of air purification technologies.